Capacity Planning in the Semiconductor Industry: Dual-Mode Procurement with Options - Peng, Chen; Erhun, Feryal; Hertzler, Erik F.; Kempf, Karl G. (Manufacturing and Service Operations Management, 2012)
To help a firm reduce inefficiencies associated with equipment capacity planning, we propose a dual-mode equipment procurement (DMEP) framework. DMEP combines dual-source (i.e., a less-expensive-but-slower base mode and a faster-but-more-expensive flexible mode) procurement with option contracts in three layers: a contract negotiation layer, where the firm chooses the best combination of lead time and price for each mode from the supply contract menu; a capacity reservation layer, where the firm reserves total equipment procurement quantities from the two supply modes before the planning horizon starts; and an execution layer, where the firm orders equipment from the two supply modes based on the updated demand information. We first investigate the execution layer as a dynamic dual-source capacity expansion problem with demand backlogging and demonstrate that the optimal policy lacks structure even under the simplest setting. Thus, we propose a heuristic solution for the execution-layer problem, which also serves as a building block for the other two layers. Through numerical analysis, we quantify the value of the added flexibility of DMEP for the firm. The DMEP framework has been implemented at Intel Corporation and has resulted in savings of tens of millions of dollars for one process technology.